Emissão de CO2 em um latossolo vermelho coberto com palha sob aplicação de efluente e lodo de esgoto - Rodrigues, Gilberto Aparecido [UNESP] (2015)
Quantifying CO2 emissions due to the applications of sewage sludge (SS) and trated sewage effluent (TSE) is important because such waste is currently being used in agriculture more often. Information on how much CO2 can be emitted when applied to the soil can contribute to future inventories of greenhouse gases. The aim of this study was to quantify the CO2 emission due to the application of straw, SS and TSE in an Oxisol of the Faculty of Agricultural Science and Veterinary of Jaboticabal-SP. Two experiments were conducted in a factorial 2 x 3, in a randomized block design. In one of the experiments, the treatments consisted of SS application (no sewage sludge and with sewage sludge, 10 Mg ha-1) and irrigation (L1: 20 mm, L2 110 mm, L3 184 mm). In another experiment, treatments consisted of application of Brachiaria brizantha straw (without straw and with straw, 10 Mg ha-1) and irrigation with 3 TSE fractions in water (F1: 11%, F2: 60% and F3: 100% of TSE). The results over 23 days of evaluation revealed that the soil with SS application had 9,34% increase in CO2 emission and 2% increase in temperature and 2,59% reduction in pH, as compared to treatments without SS application. The application of straw, combined with irrigation with TSE, increased CO2 emissions, temperature and soil moisture 8,9%, 3,1% and 12,98%, respectively, compared to treatment without application of straw. Larger fractions of TSE in water resulted in higher CO2 emissions and higher organic matter content in the soil